Study of Two Dose Regimens of Ticagrelor Compared With Clopidogrel in Patients Undergoing Percutaneous Coronary Intervention for Stable Coronary Artery Disease. Issue 13 (25th September 2018) - Orme, Rachel C.; Parker, William A.E.; Thomas, Mark R.; Judge, Heather M.; Baster, Kathleen; Sumaya, Wael; Morgan, Kenneth P.; McMellon, Hannah C.; Richardson, James D.; Grech, Ever D.; Wheeldon, Nigel M.; Hall, Ian R.; et al.
Abstract : Background: Ticagrelor has superior efficacy to clopidogrel in the management of acute coronary syndromes but has not been assessed in patients undergoing percutaneous coronary intervention for stable coronary artery disease. We compared the pharmacodynamic effects of ticagrelor and clopidogrel in this stable population. Methods: One hundred eighty aspirin-treated stable coronary artery disease patients, who were planned to undergo elective percutaneous coronary intervention in a single center, were randomized 1:1:1 to either a standard clopidogrel regimen or 1 of 2 regimens of ticagrelor, either 90 mg (T90) or 60 mg twice daily (T60), both with a 180 mg loading dose. Cellular adenosine uptake was assessed, at the time of the procedure and pre- and postdose at 1 month, by adding adenosine 1 µmol/L to aliquots of anticoagulated whole blood and mixing with a stop solution at 0, 15, 30, and 60 seconds, then measuring residual plasma adenosine concentration by high-performance liquid chromatography. Systemic plasma adenosine concentration and platelet reactivity were assessed at the same timepoints. High-sensitivity troponin T was measured pre- and 18 to 24 hours postpercutaneous coronary intervention. Results: One hundred seventy-four patients underwent an invasive procedure, of whom 162 received percutaneous coronary intervention (mean age 65 years, 18% female, 21% with diabetes mellitus). No effect on in vitro adenosine uptake was seen postdose at 1 month for either ticagrelor dose compared with clopidogrel (residual adenosine at 15 seconds, mean±SD: clopidogrel 0.274±0.101 µmol/L; T90 0.278±0.134 µmol/L; T60 0.288±0.149 µmol/L; P =0.37). Similarly, no effect of ticagrelor on in vitro adenosine uptake was seen at other timepoints, nor was plasma adenosine concentration affected (all P >0.1). Both maintenance doses of ticagrelor achieved more potent and consistent platelet inhibition than clopidogrel (VerifyNow P2Y12 reaction units, 1 month, mean±SD: predose, T60: 62±47, T90: 40±38, clopidogrel 181±44; postdose, T60: 34±30, T90: 24±21, clopidogrel 159±57; all P <0.0001 for ticagrelor versus clopidogrel). High platelet reactivity was markedly less with both T60 and T90 compared with clopidogrel (VerifyNow P2Y12 reaction units>208, 1 month postdose: 0%, 0%, and 21%, respectively). Median (interquartile range) high-sensitivity troponin T increased 16.9 (6.5–46.9) ng/L for clopidogrel, 22.4 (5.5–53.8) ng/L for T60, and 17.7 (8.1–43.5) ng/L for T90 ( P =0.95). There was a trend toward less dyspnea with T60 versus T90 (7.1% versus 19.0%; P =0.09). Conclusions: Maintenance therapy with T60 or T90 had no detectable effect on cellular adenosine uptake at 1 month, nor was there any effect on systemic plasma adenosine levels. Both regimens of ticagrelor achieved greater and more consistent platelet inhibition than clopidogrel but did not appear to affect troponin release after percutaneous coronary intervention. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02327624. Abstract : Supplemental Digital Content is available in the text.